Photoperiod, temperature, gibberellin, and an anti-gibberellin affect tuberization of potato stem segments in vitro. - Escalante-Zumaeta, B.S. (1998)
Katahdin' potato plants were grown under conditions that did not induce tuberization (noninducing conditions) and the foliage was sprayed with either a growth retardant (BAS-111) at 1000 mg·L ⁻¹ or distilled water. Other plants, grown under tuber-inducing conditions, received a foliar spray of gibberellic acid (GA 3 ) at 100 mg·L ⁻¹ or distilled water. After 1 week, treatments were repeated. Two-node stem segments were excised from the apical, subapical, medial, and basal sections of each plant 72 hours after the second foliar treatment, disinfested, and inserted into flasks containing 50 mL of Murashige and Skoog medium (2% sucrose). After 3 weeks in a darkened incubator adjusted to 24 °C, tuberization response was evaluated. Orthogonal contrasts revealed significant differences between induced and noninduced controls for tuber number, diameter, and fresh mass. BAS-111 reduced rhizome length and increased tuber number, diameter, and fresh mass. GA 3 increased rhizome length, but reduced tuber number, diameter, and fresh mass. Node location influenced tuber development, as basal explants produced significantly more and larger tubers, as well as longer rhizomes, than did apical explants, and subapical segments produced more and larger tubers than did apical segments. There were no significant differences between medial and basal nodal segments with respect to tuber number or tuber/rhizome size. Chemical names used: 1-phenoxy-5,5-dimethyl-3-(1,2,4-triazol-1-yl)-hexan-5-ol (BAS-111); 2,4a,7-trihydroxy-1-methyl-8-methylenegibb-3-ene-1,10-carboxylic acid 1->4 lactone (GA 3 ).